Trends in Cerebrovascular Surgery and Interventions - Esposito, Giuseppe; Regli, Luca; Cenzato, Marco; Kaku, Yasuhiko; Tanaka, Michihiro; Tsukahara, Tetsuya (Acta Neurochirurgica Supplement, 2021)
This is an open access proceeding book of 9th European-Japanese Cerebrovascular Congress at Milan 2018. Since many experts from Europe and Japan had very important and fruitful discussion on the management of Cerebrovascular diseases, the proceeding book is very attractive for the physician and scientists of the area.